The River Conservation for Environmental Preservation in Juristical Perspective - Sutrisno, Endang; Sugiarti , Taty; Isnaeni Nurwanty, Iis (International Journal of Psychosocial Rehabilitation, 2020)
The river conservation has become a challenge to human life nowadays. A river is a place where water has the right to flow; therefore, the environmental conditions must be maintained. In a certain context, the Indonesian public’s perception makes the river an inevitable target in economy-social needs fulfilment. This study uses a normative juridical approach based on the legal norms of government regulation number 35 of 1991 applied to rivers and regulation number 32 of 2009 concerning the environment’s protection and management, by researching the relation between positive law and reality in the community. The damaged quality of the river environment condition has an impact on all components of life structure in the river area; it must be avoided, considered the alternative use of legal instruments to build discipline. The environment issue in developing countries such as Indonesia is caused by efforts to maximize natural resources to fulfil community economic needs. Poverty becomes one factor causing the degradation of the quality of a river’s environment; this reflects economic penetration, which takes effect so much into the law dimension. The efforts used to maintain the quality of river conditions through law enforcement processes and also to coordinate the institutional function through supervision so that the preservation of the river’s environment is maintained.